DETERMINAN SOSIODEMOGRAFI DAN AKSES PELAYANAN TERHADAP KETERLAMBATAN ANC TRIMESTER PERTAMA PADA IBU HAMIL DI WAGIR, MALANG - Susi Milwati (PT Nuansa Fajar Cemerlang, 2026)
First-trimester antenatal care (ANC) visits before 12 weeks of gestation are crucial for early detection of pregnancy risks and prevention of complications. However, delays in initiating the first ANC visit still occur among some pregnant women. This study aimed to analyze the sociodemographic determinants and service access affecting delayed first-trimester ANC visits in Wagir, Malang. A quantitative descriptive study with a cross-sectional design was conducted among 37 pregnant women who attended their first ANC visit after 12 weeks of gestation, selected using total sampling. Data were collected using structured questionnaires and analyzed descriptively and through path analysis to identify the influence of variables. Results indicated that most respondents were aged 20–35 years (75.7%), had parity of 2–5 children (59.5%), completed junior high school education (43%), were unemployed (62.2%), had good knowledge (43%), and positive attitudes (54.1%). Regarding service access, 56.8% reported adequate distance and facility availability. Path analysis revealed that sociodemographic factors and service access significantly influenced delayed first-trimester ANC visits. In conclusion, delays in first-trimester ANC visits are affected by maternal sociodemographic characteristics and health service access. Strengthening pregnancy education programs and improving service access from preconception or early pregnancy stages is recommended according to maternal profiles.